(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
The rupture of the coexistence between Christians and Jews at the end of the Hispanic Middle Ages favoured the anthropological analysis of the relationships between these two communities. Thus, the social and religious conflicts motivated the development of studies on identity and otherness. Therefore, our interest consists in how the Christian majority considered the Jewish minority, and what image was created to define the “other”. Our hypothesis is that the image of the Jew was full of stereotypes collected in the lexicon. The objective of this paper is to analyze the image of the Jews in the Spanish proverb by means of a corpus of proverbs and to observe the negative connotations represented around economic and religious issues. To do this, we selected the lexical combinations of the proverbs that have a negative connotation towards the Jews and that allow us to know the explanation and origin of this phenomenon.